2004
DOI: 10.1023/b:comh.0000035229.20557.5c
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Behavioral Model in Predicting Service Utilization by Individuals Suffering from Severe Mental Illness and Homelessness

Abstract: This study compared the effectiveness of the behavioral model to predict two service utilization variables: case manager visits and total services used. Nearly 4000 individuals who were homeless and suffered from severe mental illness provided data for the study. Enabling variables explained more variance of both service utilization variables than predisposing or need variables. Social support from professionals was the strongest predictor for both service utilization variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 21 publications
7
46
2
Order By: Relevance
“…However, this is consistent with findings in most previous studies on the behavioral model's ability to predict service use [12,13]. In addition, the study did not include the full spectrum of psychiatric disorders such as schizophrenia which may account for a greater utilization of resources, especially specialized care [26].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, this is consistent with findings in most previous studies on the behavioral model's ability to predict service use [12,13]. In addition, the study did not include the full spectrum of psychiatric disorders such as schizophrenia which may account for a greater utilization of resources, especially specialized care [26].…”
Section: Discussionsupporting
confidence: 87%
“…It is to be expected that persons with a greater number of mental and/or dependence disorders would consult various primary care and specialized healthcare services. Several authors have pointed out the association between service consumption and number of psychiatric disorders [2,12]. Persons with multiple mental and/or dependence disorders present a higher level of psychological distress [27], poorer functioning [28] and increased risk of suicide [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, males use services less often than females, in the same way that individuals with substance dependence only use fewer services than those having cooccurring substance dependence and mental disorders (Rush et al 2010). This may be because males tend to wait for a sharp deterioration of their condition before seeking help (Lemming & Calsyn 2004;Lipsky et al 2010;Putkonen et al 2010;Wang et al 2005a). Class 2 participants perceived their physical health as good to excellent, which indicates that they do not see themselves as sick and thus needing care.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to country of birth, race, and ethnicity, studies found that Caucasians are more likely to use health services than Blacks or immigrants (Vasiliadis et al, 2007;Hatzenbuehler et al, 2008;Keyes et al, 2008). Professional and social support (including family and friends) also plays a role (Lemming & Calsyn, 2004;Bonin et al, 2007). Social support can be positively or negatively associated with service utilization for mental healthcare reasons (Carr et al, 2003;Pescosolido et al, 1998;Albert et al, 1998).…”
Section: Determinants Of Service Utilization Of Patient With Mental Dmentioning
confidence: 99%